Sugar and fodder beets agronomic evaluation - Santos, Henrique Pereira dos; Lhamby, Júlio Cesar B. (Pesquisa Agropecuaria Brasileira, 2014)
During a four-year period of experimentation at the Centro Nacional de Pesquisa de Trigo at Passo Fundo, RS, Brazil, several beet cultivars showed good adaptation to the conditions in the region of the highlands of the state of Rio Grande do Sul. Root yields (34 t/ha) and sugar content (16.4%) were, respectively, near and superior to traditionally producer countries (30 t/ha e 15%). Hence, beets may be considered an alternative crop for alcohol production in this region. Estimated average yield of alcohol reached 2,771 liters/ha.